Study on the coupling between the hanging- and foot-wall beds and the gas content of deep coal seams in the Linxing area, eastern margin of the Ordos Basin - HUO Shaowei; FENG Xingqiang; WU Jian; ZHANG Shouren; ZHOU Lei; QIAN Zhuliang; CHAO Weiwei (Dizhi lixue xuebao)
Objective  The deep coalbed methane in the Linxing area at the eastern margin of the Ordos Basin has great potential for exploration and development and has become a key exploration and development target. Research shows that the hanging- and foot-wall beds of the coal seams play an important role in the enrichment and preservation of coalbed methane. At present, there is lack of systematic research on the influence of the hanging- and foot-wall beds of deep coal seams on the gas content, and the coupling between them is not clear. This study aims to extend the theory of methane enrichment in deep coal beds.   Method  Through the comprehensive application of logging, drilling, and mud logging data and the use of the Analytic Hierarchy Process (AHP), the coupling between the characteristics of the hanging- and foot-wall beds of the No. 8+9 coal seam and its gas-bearing property were studied.   Results  The research results are as follows: (1) In the Linxing area, the Benxi Formation–Taiyuan Formation developed in a barrier-tidal flat-lagoon sedimentary system. The No. 8+9 coal seam mainly developed in the supratidal zone, peat flat, and peat swamp, and the sedimentary environments of the hanging- and foot-wall beds are sedimentary microfacies such as mud flat, lagoon, ash flat, and sand flat. (2) Influenced by the sedimentary environments, the hanging- and foot-wall beds are mainly composed of three lithologies, namely limestone, mudstone, and sandstone. The thicknesses of the hanging- and foot-wall beds of the coal seam vary greatly along the lateral extent. The thickness of the hanging-wall bed ranges from 1.90 to 19.00 m, and the thickness of the foot-wall bed ranges from 1.99 to 21.19 m. There are seven different lithological combinations of the hanging- and foot-wall beds, including top-limestone bottom-mud, top-mud bottom-limestone, top-mud bottom-mud, top-mud bottom-sand, top-sand bottom-limestone, top-sand bottom-mud, and top-sand bottom-sand. (3) Further research on the relationship between the characteristics of the hanging- and foot-wall and the gas content of the coal seam shows that the coal seams in top-limestone bottom-mud, top-mud bottom-limestone, and top-mud bottom-mud associations exhibit the highest gas contents; the coal seams in top-mud bottom-sand and top-sand bottom-limestone associations exhibit relatively high gas contents; the coal seams in top-sand bottom-mud and top-sand bottom-sand associations exhibit low gas contents. Within the same lithology, the greater the thickness of the hanging- and foot-wall beds, the higher the gas content of the coal seam, and there is a positive correlation between the thicknesses of the hanging- and foot-wall beds and the gas content.   Conclusion  According to the research results, three types of coupling models between the hanging- and foot-wall of deep coal seams and their gas-bearing properties are distinguished: Type I (good coupling) with a gas content of more than 15 m³/t, Type II (relatively good coupling) with a gas content of 12 to 15 m³/t, and Type III (poor coupling) with a gas content of less than 12 m³/t. [Significance] The research results have clarified the controlling effect of the hanging- and foot-wall beds of deep coal seams on the gas content, which has important significance for guiding the evaluation, optimization, and mining of areas favorable for deep coalbed methane, and further extends the theory of deep coalbed methane enrichment.